Detection of bovine mastitis pathogens by loop-mediated isothermal amplification and an electrochemical DNA chip - KAWAI, Kazuhiro; INADA, Mika; ITO, Keiko; HASHIMOTO, Koji; NIKAIDO, Masaru; HATA, Eiji; KATSUDA, Ken; KIKU, Yoshio; TAGAWA, Yuichi; HAYASHI, Tomohito (Journal of Veterinary Medical Science, 2017)
Bovine mastitis causes significant economic losses in the dairy industry. Effective prevention of bovine mastitis requires an understanding of the infection status of a pathogenic microorganism in a herd that has not yet shown clinical signs of mastitis and appropriate treatment specific for the pathogenic microorganism. However, bacterial identification by culture has drawbacks in that the sensitivity may be low and the procedure can be complex. In this study, we developed a genetic detection method to identify mastitis pathogens using a simple and highly sensitive electrochemical DNA chip which can specifically detect bacterial DNA in milk specimens. First, we selected microorganisms belonging to 12 families and/or genera associated with mastitis for which testing should be performed. Next, we optimized the conditions for amplifying microorganism DNA by loop-mediated isothermal amplification (LAMP) using 32 primers and the use of a DNA chip capable of measuring all pathogens simultaneously. Sample detection could be completed in just a few hours using this method. Comparison of the results obtained with our DNA chip method and those obtained by bacterial culture verified that when the culture method was set to 100%, the total positive concordance rate of the DNA chip was 85.0% and the total negative concordance rate was 86.9%. Furthermore, the proposed method allows both rapid and highly sensitive detection of mastitis pathogens. We believe that this method will contribute to the development of an effective mastitis control program.